Composite material and preparation method thereof, photoelectric device and display device

By adding nitrogen oxygen radical compounds to inorganic semiconductor materials, the defects on the surface of the material are passivated, and the problem of low carrier transmission efficiency of the material is solved, achieving higher luminescence efficiency and stability.

CN119730569APending Publication Date: 2025-03-28TCL TECHNOLOGY GROUP CORPORATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311281799.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

There are a large number of defects on the surface of existing inorganic semiconductor materials, which reduces carrier transmission efficiency and affects the application of materials.

Method used

By adding an nitrogen-oxygen radical compound as the first material, the metal ions whose oxygen atoms are uncoordinated on the surface of the inorganic semiconductor particles are coordinated to passivate surface defects, thereby improving the film formation effect, stability and carrier transport performance of the material.

Benefits of technology

Effectively passivating defects on the surface of inorganic semiconductor particles improves the luminous efficiency and stability of the device and extends the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730569A_ABST
    Figure CN119730569A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a photoelectric device and a display device.The composite material comprises inorganic semiconductor particles and a first material, and the first material comprises one or more of compounds with the structure shown in the formula (1). According to the composite material provided by the invention, the nitroxide free radical compound is added, and oxygen in the compound can be coordinated with uncoordinated metal ions on the surfaces of inorganic semiconductor particles, so that an effect of passivating surface defects is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor technology, and in particular to a composite material and a preparation method thereof, an optoelectronic device and a display device. Background Art

[0002] Inorganic semiconductor particles refer to inorganic materials with semiconductor properties, such as zinc oxide nanoparticles, molybdenum oxide nanoparticles, cadmium sulfide nanoparticles, etc. Most of these materials have excellent carrier injection or transport properties and are widely used in semiconductor devices.

[0003] However, existing inorganic semiconductor materials have a large number of defects on their surfaces, which reduce the carrier transfer efficiency and thus affect the application of the materials. Summary of the invention

[0004] In view of this, the present application provides a composite material and a preparation method thereof, an optoelectronic device and a display device, which are intended to passivate defects on the surface of inorganic semiconductor particles.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present application provides a composite material, comprising inorganic semiconductor particles and a first material, wherein the first material comprises one or more compounds having a structure represented by formula (1);

[0007]

[0008] Wherein, Y is selected from one or more combinations of hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C20 alkylcarbonyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted aryl having 5 to 60 ring atoms, substituted or unsubstituted heteroaryl having 5 to 60 ring atoms, substituted or unsubstituted aryloxy having 5 to 60 ring atoms, substituted or unsubstituted heteroaryloxy having 5 to 60 ring atoms, wherein the substituent includes one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, C1-C10 alkylcarbonyl;

[0009] R1, R2, R3, and R4 are each independently selected from C1-C10 alkyl groups.

[0010] Optionally, in some embodiments of the present application, Y is selected from one of hydrogen, hydroxyl, C1-C6 alkyl, C1-C6 alkoxy, and NR5R6, wherein R5 and R6 are each independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, and C1-C6 alkylcarbonyl; and / or,

[0011] R1, R2, R3, and R4 are each independently selected from C1-C4 alkyl groups.

[0012] Optionally, in some embodiments of the present application, Y is selected from one of H, hydroxyl, C1-C3 alkyl, C1-C3 alkoxy, and NR5R6; and / or,

[0013] R5 and R6 are each independently selected from H or C1-C2 alkylcarbonyl.

[0014] Optionally, in some embodiments of the present application, the first material includes one or more of the compounds shown in any one of formulas (2) to (6):

[0015]

[0016] Optionally, in some embodiments of the present application, in the composite material, the molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1).

[0017] Optionally, in some embodiments of the present application, the average particle size of the inorganic semiconductor particles is 2 to 20 nm.

[0018] Optionally, in some embodiments of the present application, the inorganic semiconductor particles are selected from N-type inorganic semiconductor particles, and the N-type inorganic semiconductor particles are selected from one or more of metal oxides and doped metal oxides; the metal oxides include one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxides in the doped metal oxides include multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; or,

[0019] The inorganic semiconductor particles are selected from P-type inorganic semiconductor particles, and the P-type inorganic semiconductor particles are selected from at least one of nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; or,

[0020] The inorganic semiconductor particles are selected from quantum dot luminescent materials, and the quantum dot luminescent materials include at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds; the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnS At least one of CdS, ZnSe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe e, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, At least one of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0021] In a second aspect, the present application also proposes a method for preparing a composite material, the preparation method comprising the following steps:

[0022] Providing inorganic semiconductor particles, a first material and a first solvent;

[0023] Mixing the inorganic semiconductor particles, the first material and the first solvent to obtain a composite material;

[0024] Wherein, the first material includes one or more compounds having a structure shown in formula (1);

[0025]

[0026] Wherein, Y is selected from one or more combinations of hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C20 alkylcarbonyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted aryl having 5 to 60 ring atoms, substituted or unsubstituted heteroaryl having 5 to 60 ring atoms, substituted or unsubstituted aryloxy having 5 to 60 ring atoms, substituted or unsubstituted heteroaryloxy having 5 to 60 ring atoms, wherein the substituent includes one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, C1-C10 alkylcarbonyl;

[0027] R1, R2, R3, and R4 are each independently selected from C1-C10 alkyl groups.

[0028] Optionally, in some embodiments of the present application, the molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1); and / or,

[0029] The first material includes one or more compounds represented by any one of formulas (2) to (6):

[0030]

[0031] Optionally, in some embodiments of the present application, when the inorganic semiconductor particles include N-type inorganic semiconductor particles, the first solvent includes one or more of C1 to C5 alcohol solvents; or,

[0032] When the inorganic semiconductor particles include P-type inorganic semiconductor particles, the first solvent includes one or more of chloroform, chlorobenzene, and dichlorobenzene; or

[0033] When the inorganic semiconductor particles include quantum dot luminescent materials, the first solvent includes one or more of n-hexane, n-octane, n-heptane, cyclohexane, and cyclopentane.

[0034] Optionally, in some embodiments of the present application, the step of mixing the inorganic semiconductor particles, the first material and the first solvent to obtain a composite material includes:

[0035] The inorganic semiconductor particles, the first material and the first solvent are mixed, and then ultrasonicated for 10 to 240 minutes to obtain a composite material.

[0036] In a third aspect, the present application also proposes a photoelectric device, comprising a first electrode, a functional layer and a second electrode, wherein the functional layer comprises at least one first functional layer, and the materials of the at least one first functional layer are independently selected from composite materials, and the composite materials include the composite materials described above, or include the composite materials prepared by the preparation method described above.

[0037] Optionally, in some embodiments of the present application, the first electrode and the second electrode are each independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or,

[0038] The thickness of the first functional layer is 10 to 1000 nm; and / or,

[0039] The functional layer further includes a second functional layer, which includes one or more of an electron injection layer, an electron transport layer, a light emitting layer, a hole transport layer, and a hole injection layer.

[0040] Optionally, in some embodiments of the present application, when the second functional layer includes the electron injection layer and / or the electron transport layer, the material of the electron injection layer and / or the electron transport layer includes an inorganic material and / or an organic material; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or,

[0041] When the second functional layer includes the hole transport layer, the material of the hole transport layer includes 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, tris(3-methylphenylphenylamino)-triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] and poly(4-butylphenyl-diphenylamine). at least one of one or more of poly(vinylamine), polyaniline, polypyrrole, poly(p-phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, and spiro NPB; and / or,

[0042] When the second functional layer includes the hole injection layer, the material of the hole injection layer includes poly(ethylenedioxythiophene): polystyrene sulfonate, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tri[phenyl(m- One or more of: [(4-(diphenylamino)-1,4-tolyl)amino]triphenylamine, 4,4',4"-tri(N-carbazolyl)-triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile; and / or,

[0043] When the second functional layer includes a light-emitting layer, the material of the light-emitting layer includes one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium, poly[(9,9-dioctylfluorene-2,7-diyl)-alternate-(2,1,3-benzothiadiazole-4,7-diyl)], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, T One or more of BPe fluorescent material, TTPX fluorescent material, TBRb fluorescent material, DBP fluorescent material, delayed fluorescent material, TTA material, thermally activated delayed material, polymer containing BN covalent bond, hybrid localized charge transfer excited state material, and exciplex luminescent material, the quantum dot luminescent material is selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are selected from II-VI group compounds, IV-VI group compounds, III - at least one of a Group V compound and a Group I-III-VI compound; the Group II-VI compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZn At least one of SeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH 3+ or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0044] In a fourth aspect, the present application further proposes a display device, comprising the optoelectronic device as described above.

[0045] The composite material proposed in the present application is added with a nitroxide free radical compound, the oxygen in which can coordinate with the uncoordinated metal ions on the surface of the inorganic semiconductor particles, play a role in passivating surface defects, and thus improve the luminous efficiency of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 is a schematic structural diagram of an optoelectronic device proposed in an embodiment of the present application;

[0048] Figure 2 is a schematic structural diagram of an optoelectronic device proposed in one embodiment of the present application;

[0049] Figure 3 is a schematic structural diagram of a photoelectric device proposed in another embodiment of the present application;

[0050] Reference numerals:

[0051] 100 - photoelectric device; 10 - anode; 20 - light-emitting layer; 30 - electron transport layer; 40 - cathode; 50 - hole transport layer; 60 - hole injection layer. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0053] In this application, unless otherwise specified, directional words such as "upper" and "lower" used refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".

[0054] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0055] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0056] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0057] Explanation of terms

[0058] In the present application, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it is understood that the defined group may be substituted by one or more substituents. When substituted by multiple substituents, each substituent may be the same or different.

[0059] In the present application, "alkyl" may represent a straight chain alkyl or a branched chain alkyl. C1-10 alkyl refers to an alkyl group containing 1 to 10 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl or C10 alkyl. Non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylpentyl, 3-methylpentyl, n-hexyl, etc.

[0060] In the present application, "aryl" refers to a group derived from an aromatic ring compound containing a benzene ring by removing one hydrogen. The aromatic ring compound can be a single-ring aromatic ring, a condensed aromatic ring formed by a plurality of rings, or a non-condensed aromatic ring connected by a plurality of rings. For a polycyclic ring, at least one is an aromatic ring system. Suitable examples of aromatic ring compounds include, but are not limited to, benzene rings, naphthalene rings, biphenyl rings, anthracene rings, phenanthrene rings, naphthacene rings, fluorene rings, indene, etc. Correspondingly, the aryl groups corresponding to the above aromatic ring compounds are phenyl, naphthyl, biphenyl, anthracene, phenanthrene, naphthacene ring group, fluorene group, indenyl, etc.

[0061] In the present application, "heteroaryl" refers to a group derived from a heterocycle by removing a hydrogen atom. A heterocycle refers to an aromatic ring in which at least one carbon atom is replaced by a non-carbon atom. The non-carbon atom may be an N atom, an O atom, an S atom, a P atom, etc., and the number of non-carbon atoms may be 1 to 10. Suitable examples include, but are not limited to, thiophene, furan, pyrrole, imidazole, diazole, triazole, pyridine, bipyridine, pyrimidine, triazine, acridine, pyridazine, pyrazine, quinoline, isoquinoline, quinazoline, quinoxaline, phthalazine, pyridopyrimidine, pyridopyrazine, benzothiophene, benzofuran, indole, pyrroloimidazole, pyrrolopyrrole, thienopyrrole, thienothiophene, furopyrrole, furanofuran, thienofuran, benzisoxazole, benzisothiazole, benzimidazole, o-naphthyridine, phenanthridine, primary idine, quinazolinone, dibenzothiophene, dibenzofuran, carbazole, and derivatives thereof.

[0062] In the present application, an alkoxy group has a structural feature of the formula -OR; an aryloxy group or a heteroaryloxy group has a structural feature of the formula -OAr, wherein Ar refers to an aryl group or a heteroaryl group; an amino group refers to -NR 1 R 2 ; hydroxyl refers to -OH; carboxyl refers to -COOH; nitro refers to -NO2; mercapto refers to -SH; cyano refers to -CN; sulfonic acid refers to -SO3H; alkylcarbonyl refers to Halogen atoms refer to -F, -Br, -Cl or -I. Wherein, R is selected from alkyl; 1 , R 2Each is independently selected from H, or substituted or unsubstituted alkyl, and the substituent includes but is not limited to one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, and C1-C10 alkylcarbonyl.

[0063] In a first aspect, an embodiment of the present application provides a composite material, the composite material comprising inorganic semiconductor particles and a first material, wherein the first material comprises one or more compounds having a structure represented by formula (1);

[0064]

[0065] Wherein, Y is selected from one or more combinations of hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C20 alkylcarbonyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted aryl having 5 to 60 ring atoms, substituted or unsubstituted heteroaryl having 5 to 60 ring atoms, substituted or unsubstituted aryloxy having 5 to 60 ring atoms, substituted or unsubstituted heteroaryloxy having 5 to 60 ring atoms, wherein the substituent includes one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, C1-C10 alkylcarbonyl;

[0066] R1, R2, R3, and R4 are each independently selected from C1-C10 alkyl groups.

[0067] In some embodiments, Y is selected from one of H, hydroxyl, C1-C6 alkyl, C1-C6 alkoxy, and NR5R6; wherein R5 and R6 are each independently selected from one of H, C1-C6 alkyl, C1-C6 alkoxy, and C1-C6 alkylcarbonyl.

[0068] The compound represented by formula (1) is a nitroxide free radical compound, in which the unpaired electrons occupy a molecular orbital composed of the Px orbitals of nitrogen and oxygen, and most of the unpaired electron density is localized on the nitrogen atom.

[0069] The composite material proposed in the present application is added with a nitroxide free radical compound, the oxygen in which can coordinate with the uncoordinated metal ions on the surface of the inorganic semiconductor particles, play a role in passivating surface defects, help improve the film-forming effect of the material, and enhance the stability of the material and the carrier transport performance.

[0070] In some embodiments, Y is selected from one of H, hydroxyl, C1-C3 alkyl, C1-C3 alkoxy, and NR5R6.

[0071] In some embodiments, R5 and R6 are each independently selected from H or C1-C2 alkylcarbonyl.

[0072] In some embodiments, R1, R2, R3, and R4 are each independently selected from C1-C4 alkyl.

[0073] Further, in some specific embodiments, the first material includes one or more of the compounds shown in any one of formulas (2) to (6): wherein the compound shown in formula (2) is 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO, CAS: 2564-83-2); the compound shown in formula (3) is 4-amino-2,2,6,6-tetramethylpiperidinyl 1-oxyl free radical (CAS: 14691-88-4); the compound shown in formula (4) is 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitrogen oxide free radical (CAS: 2226-96-2); the compound shown in formula (5) is 4-acetylamino-2,2,6,6-tetramethylpiperidinyl-1-oxyl free radical (CAS: 14691-89-5); the compound shown in formula (6) is 4-methoxy-tetramethylpiperidinyl oxide free radical (CAS: 95407-69-5).

[0074]

[0075] In some embodiments, the inorganic semiconductor particles may be N-type inorganic semiconductor particles with electron transport properties, or P-type inorganic semiconductor particles with hole transport properties, or quantum dot luminescent materials with fluorescent luminescence properties.

[0076] When the inorganic semiconductor particles are selected from P-type inorganic semiconductor particles, the composite material includes P-type inorganic semiconductor particles and the first material. The composite material can be used to make a hole functional layer of the optoelectronic device 100, and the hole functional layer includes one or two layers of the hole transport layer 50 and the hole injection layer 60.

[0077] When the inorganic semiconductor particles are selected from quantum dot luminescent materials, the composite material includes the quantum dot luminescent material and the first material. The composite material can be used to make the luminescent layer 20 of the optoelectronic device 100 .

[0078] When the inorganic semiconductor particles are selected from N-type inorganic semiconductor particles, the composite material includes N-type inorganic semiconductor particles and a first material. The composite material can be used to make the electron transport layer 30 of the optoelectronic device 100. By adding the first material, on the one hand, the defects on the surface of the N-type inorganic semiconductor particles can be passivated to avoid the formation of electron capture centers and exciton recombination centers on their surfaces, which helps to improve the electron transport efficiency. When the electron transport layer 30 is prepared, it can promote the effective transmission of electrons to the light-emitting layer 20 to recombine with holes, thereby improving the luminous efficiency of the device; on the other hand, the first material also has a high electron-donating property, which can also improve the conductivity and transport performance of the material, thereby improving the optoelectronic performance of the device.

[0079] In some embodiments, the P-type inorganic semiconductor particles can be a material commonly found in the art and having hole transport properties, for example, including but not limited to at least one of nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0080] In some embodiments, the quantum dot luminescent material may include but is not limited to at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material; the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound; the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, C At least one of dSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, S At least one of nTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, At least one of AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.

[0081] As an example, the core-shell structured quantum dots may be selected from but not limited to at least one of CdZnSe / CdZnSe / ZnSe / CdZnS / ZnS, CdZnSe / CdZnSe / CdZnS / ZnSCdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0082] It should be noted that, for the material of the aforementioned single structure quantum dot, or the material of the core of the core-shell structure quantum dot, or the material of the shell of the core-shell structure quantum dot, the chemical formula provided only indicates the elemental composition, but does not indicate the content of each element. For example, CdZnSe only indicates that it is composed of three elements, Cd, Zn and Se. If the content of each element is indicated, it corresponds to Cd x Zn 1-x Se,0 <x<1。

[0083] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0084] In some embodiments, the N-type inorganic semiconductor particles can be a material commonly used in the art and having electron transport properties, for example, can include but are not limited to one or more of metal oxides and doped metal oxides; the metal oxides include one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxides in the doped metal oxides include multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0085] In some embodiments, in the composite material, the molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1); for example, it can be 1:0.01, 1:0.02, 1:0.05, 1:0.07, 1:0.09, 1:0.1, and values ​​between any two of the above values. Controlling the addition amount of the first material within this range can effectively passivate the defects on the surface of the inorganic semiconductor particles.

[0086] In some embodiments, the average particle size of the inorganic semiconductor particles is 2 to 20 nm; for example, it can be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, and values ​​between any two of the above values.

[0087] In the second aspect, the present application also proposes a method for preparing a composite material, see Figure 1 , the preparation method comprises the following steps:

[0088] S10, providing inorganic semiconductor particles, a first material and a first solvent, wherein the first material comprises one or more compounds having a structure represented by formula (1);

[0089] S20, mixing the inorganic semiconductor particles, the first material, and the first solvent to obtain a composite material.

[0090] The preparation method proposed in the embodiment of the present application can produce a composite material, in which the defects on the surface of the inorganic semiconductor particles are passivated by the first material, so that the composite material has better film-forming effect, stability and carrier transport performance.

[0091] In some embodiments, the nitroxide free radical compound may be a common piperidine nitroxide free radical, and the first material may include but is not limited to one, two or more of the piperidine nitroxide free radicals.

[0092] In some embodiments, the first material includes one or more compounds represented by any one of formulas (2) to (6).

[0093] In some embodiments, the inorganic semiconductor particles may be N-type inorganic semiconductor particles with electron transport properties, or P-type inorganic semiconductor particles with hole transport properties, or quantum dot luminescent materials with fluorescent luminescence properties. The specific types of the inorganic semiconductor particles are as described above and will not be described here. The specific materials can be purchased on the market or prepared by a solution method or a sol-gel method. Taking nano zinc oxide as an example, the preparation method may include the following steps: dispersing a zinc salt in an organic solvent to form a zinc solution; adding an alcohol solution of an alkali thereto, stirring to obtain a clear and transparent mixed solution; adding acetone to the mixed solution to precipitate nanoparticles, washing, centrifuging, and drying to obtain nano zinc oxide. Among them, zinc salts include but are not limited to zinc chloride, zinc nitrate, zinc acetate, etc.; alkalis include but are not limited to sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, etc.; alcohols include but are not limited to methanol, ethanol, etc.; organic solvents include but are not limited to DMSO, DMF, etc. In addition, in the zinc solution, the zinc ion concentration is 0.1 to 1 mol / L; the amount of the alcohol solution of the alkali added satisfies: OH - With Zn 2+ The molar ratio is (1.5-3.0):1; the stirring time is 1-4h.

[0094] In some embodiments, the addition amount of the first material and the inorganic semiconductor particles satisfies: the molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1), for example, it can be 1:0.01, 1:0.02, 1:0.05, 1:0.07, 1:0.09, 1:0.1 and values ​​between any two of the above values. Adding materials within this range can produce a composite material with a content ratio of the two within an appropriate range.

[0095] In some embodiments, when the inorganic semiconductor particles include N-type inorganic semiconductor particles, the first solvent includes one or more of C1-C5 alcohol solvents; for example, it can be one or more of methanol, ethanol, isopropanol, n-butanol, and pentanol.

[0096] In some embodiments, when the inorganic semiconductor particles include P-type inorganic semiconductor particles, the first solvent includes one or more of chloroform, chlorobenzene, and dichlorobenzene.

[0097] In some embodiments, when the inorganic semiconductor particles include quantum dot light-emitting materials, the first solvent includes one or more of n-hexane, n-octane, n-heptane, cyclohexane, and cyclopentane.

[0098] In order to promote full contact and coordination between the inorganic semiconductor particles and the first material, in some embodiments, step S20 may specifically include: mixing the inorganic semiconductor particles, the first material and the first solvent, and ultrasonicating for 10 to 240 minutes to obtain a composite material.

[0099] In a third aspect, the present application further proposes an optoelectronic device 100, which may be an organic light emitting diode (OLED), a quantum dot light emitting diode (QLED), a solar cell, etc. For ease of description, the structure of the optoelectronic device 100 is specifically described below using QLED as an example.

[0100] See also Figure 2 , the photoelectric device 100 includes a first electrode, a functional layer, and a second electrode. The first electrode may be one of the anode 10 and the cathode 40, and the second electrode may be the other of the anode 10 and the cathode 40. It can be understood that the photoelectric device 100 may be an upright device or an inverted device. When it is an upright device, the photoelectric device 100 includes the anode 10, the functional layer, and the cathode 40 stacked in sequence from bottom to top; when it is an inverted device, the photoelectric device 100 includes the cathode 40, the functional layer, and the anode 10 stacked in sequence from bottom to top.

[0101] In some embodiments, the anode 10 may be an anode 10 known in the art for use in a photoelectric device 100, for example, may be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of a metal and a metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of a metal and a metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0102] The cathode 40 can be a cathode 40 for the optoelectronic device 100 known in the art, for example, can be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0103] See also Figure 3, the functional layer may be a film layer, for example, any one of the electron transport layer 30, the hole transport layer 50, the hole injection layer 60, and the light-emitting layer 20; or multiple film layers, for example, two, three or four of the electron transport layer 30, the hole transport layer 50, the hole injection layer 60, and the light-emitting layer 20. It should be noted that when the electron transport layer 30, the hole transport layer 50, the hole injection layer 60, and the light-emitting layer 20 exist at the same time, the stacking order of these four film layers is that the hole injection layer 60, the hole transport layer 50, the light-emitting layer 20, and the electron transport layer 30 are stacked in sequence from the anode 10 to the cathode 40; when one or more of the film layers do not exist, the relative position relationship of the other film layers is not affected. For example, in some embodiments, the multiple film layers are composed of the electron transport layer 30, the hole transport layer 50, and the light-emitting layer 20, and the order of the three film layers is that the hole transport layer 50, the light-emitting layer 20, and the electron transport layer 30 are stacked in sequence from the anode 10 to the cathode 40.

[0104] There is at least one special film layer in one or more film layers, and its material can be the above-mentioned composite material. Since the composite material is used to prepare the film layer, the film-forming effect and photoelectric performance of the film layer are effectively improved, thereby improving the service life and photoelectric performance of the device. For the convenience of description, this article uniformly defines this special film layer as the first functional layer.

[0105] It can be understood that any one or more of the electron transport layer 30, the hole transport layer 50, the hole injection layer 60, and the light-emitting layer 20 can be prepared using corresponding composite materials, that is, set as the first functional layer. Specifically, in some embodiments, the first functional layer is the electron transport layer 30, and correspondingly, when preparing the film layer, the composite material used includes an N-type inorganic semiconductor material and a first material; in other embodiments, the first functional layer is a hole functional layer, and correspondingly, when preparing the film layer, the composite material used includes a P-type inorganic semiconductor material and a first material; in still other embodiments, the first functional layer is the light-emitting layer 20, and correspondingly, when preparing the film layer, the composite material used includes a quantum dot light-emitting material and a first material.

[0106] The thickness of the first functional layer is 10-1000 nm; for example, it can be 10-50 nm, 10-100 nm, 10-200 nm, 20-60 nm, 20-120 nm, 20-100 nm, 50-200 nm, 50-500 nm, 500-1000 nm, etc.

[0107] In other embodiments, the functional layer is a plurality of film layers, among which some film layers are prepared by using corresponding composite materials (i.e., the first functional layer), some other film layers are left, and these remaining film layers are defined as the second functional layer, and the second functional layer can be selected from one or more of the electron injection layer, the electron transport layer, the light-emitting layer, the hole transport layer, and the hole injection layer; for example, in some embodiments, the functional layer includes four film layers, namely, the electron transport layer 30, the hole transport layer 50, the hole injection layer 60, and the light-emitting layer 20, among which only the electron transport layer 30 is prepared by using composite materials, that is, the electron transport layer 30 belongs to the first functional layer, and the other three film layers all belong to the second functional layer.

[0108] The second functional layer can be prepared using film materials commonly used in the art. Specifically:

[0109] In some embodiments, the second functional layer includes a hole functional layer, and the hole functional layer includes one or two layers of a hole transport layer 50 and a hole injection layer 60. The material of the hole functional layer can be a material commonly used in the art and has hole injection or transport properties, for example, it can include but is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (T PD), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), tris(3-methylphenylphenylamino)-triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB) and poly(4-butylphenyl-diphenylamine) (poly-TPD), polyaniline, polypyrrole, poly(p-phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, One or more of 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine (NPB), and spiro NPB.Conventional materials for the hole injection layer 60 may include, but are not limited to, poly(ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA ... One or more of 4″-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4′,4″-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N′-diphenyl-N,N′-di(1-naphthyl)-1,1′-biphenyl-4,4″-diamine (α-NPD), and hexaazatriphenylene-capronitrile (HAT-CN).

[0110] In some embodiments, the second functional layer includes an electron transport layer 30, and the common materials of the electron transport layer 30 may include but are not limited to one or more of metal oxides and doped metal oxides; the metal oxides include one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxides in the doped metal oxides include multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0111] In some embodiments, the second functional layer includes a light-emitting layer 20, and the material of the light-emitting layer 20 includes one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium, poly[(9,9-dioctylfluorene-2,7-diyl)-alternate-(2,1,3-benzothiadiazole-4,7-diyl)], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives. The invention relates to a material selected from the group consisting of a fluorene derivative, a TBPe fluorescent material, a TTPX fluorescent material, a TBRb fluorescent material, a DBP fluorescent material, a delayed fluorescent material, a TTA material, a thermally activated delayed material, a polymer containing a covalent bond of BN, a hybrid localized charge transfer excited state material, and an exciplex luminescent material. The quantum dot luminescent material is selected from at least one of a single structure quantum dot, a core-shell structure quantum dot, and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot, and the shell material of the core-shell structure quantum dot are selected from the group consisting of II-VI compounds, IV-VI compounds, at least one of a group III-V compound and a group I-III-VI compound; the group II-VI compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd At least one of ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH 3+ or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+At least one of, X is a halogen anion selected from Cl-, Br - , at least one of I-.

[0112] It is understandable that the optoelectronic device 100 may also be provided with some functional layers conventionally used in optoelectronic devices 100 that help improve the performance of the optoelectronic device 100, such as an electron injection layer, an electron blocking layer, an interface modification layer, etc.

[0113] It can be understood that the material and thickness of each layer of the optoelectronic device 100 can be adjusted according to the actual requirements of the optoelectronic device 100 .

[0114] Based on the above-mentioned embodiment of the optoelectronic device 100, a method for preparing the optoelectronic device 100 is further proposed, and the preparation method includes:

[0115] S100, providing a first electrode;

[0116] S200, providing a functional layer on the first electrode;

[0117] S300 , disposing a second electrode on the functional layer to obtain the optoelectronic device 100 .

[0118] Specifically, step S200 includes: preparing at least one film layer in sequence according to a preset order of at least one film layer to obtain a functional layer.

[0119] Among them, at least one film layer includes one or more of the light-emitting layer 20, the hole transport layer 50, the hole injection layer 60, and the electron transport layer 30. The preset order of at least one film layer can be adjusted according to the device type. For example, the film layer order of the upright device is the anode 10, the hole injection layer 60, the hole transport layer 50, the light-emitting layer 20, the electron transport layer 30, and the cathode 40 are stacked from bottom to top; accordingly, in actual preparation, the anode 10, the hole injection layer 60, the hole transport layer 50, the light-emitting layer 20, the electron transport layer 30, and the cathode 40 are prepared in sequence. The film layer order of the inverted device is opposite to that of the upright device. Accordingly, in actual preparation, the cathode 40, the electron transport layer 30, the light-emitting layer 20, the hole transport layer 50, the hole injection layer 60, and the anode 10 are prepared in sequence.

[0120] In some embodiments, each film layer can be realized by conventional techniques in the art, such as chemical methods or physical methods. Among them, chemical methods include chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. Physical methods include physical coating and solution methods, among which physical coating includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; solution methods can be spin coating, printing, inkjet printing, doctor blade coating, printing, dip-coating, immersion, spraying, roller coating, casting, slit coating, and strip coating, etc.

[0121] It should be noted that when preparing the functional layer, when the film layer to be prepared is the first functional layer, the preparation of the first functional layer includes the following steps: providing a composite material, depositing the composite material on the previous film layer, and obtaining the first functional layer.

[0122] The previous film layer refers to the film layer obtained in the previous step in the film layer preparation process.

[0123] In some embodiments, the step of depositing the composite material on the upper film layer to obtain the first functional layer includes: mixing the composite material and a second solvent to obtain a mixed solution; depositing the mixed solution on the upper film layer, and annealing to obtain the first functional layer.

[0124] In some embodiments, when the inorganic semiconductor particles include N-type inorganic semiconductor particles, the second solvent includes one or more of C1-C5 alcohol solvents; for example, it can be one or more of methanol, ethanol, isopropanol, n-butanol, and pentanol.

[0125] In some embodiments, when the inorganic semiconductor particles include P-type inorganic semiconductor particles, the second solvent includes one or more of chloroform, chlorobenzene, and dichlorobenzene.

[0126] In some embodiments, when the inorganic semiconductor particles include quantum dot light-emitting materials, the second solvent includes one or more of n-hexane, n-octane, n-heptane, cyclohexane, and cyclopentane.

[0127] In some embodiments, in the mixed solution, the concentration of the composite material is 10-40 mg / ml; for example, it can be 10 mg / ml, 20 mg / ml, 30 mg / ml, 40 mg / ml, and a value between any two of the above values.

[0128] In some embodiments, when the inorganic semiconductor particles in the composite material are N-type inorganic semiconductor particles, the annealing temperature is 80-120°C; for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C and values ​​between any two of the above values.

[0129] In some embodiments, when the inorganic semiconductor particles in the composite material are P-type inorganic semiconductor particles, the annealing temperature is 80-200°C; for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 150°C, 160°C, 180°C, 200°C and values ​​between any two of the above values.

[0130] In some embodiments, when the inorganic semiconductor particles in the composite material are quantum dot luminescent materials, the annealing temperature is 80-120°C; for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C and values ​​between any two of the above values.

[0131] In some embodiments, the annealing time is 10 to 120 min; for example, it can be 10 min, 20 min, 50 min, 80 min, 100 min, 120 min, or a value between any two of the above values.

[0132] In addition, the present application also proposes a display device, which includes the optoelectronic device 100 as described above. The display device can be any electronic product with a display function, including but not limited to smart phones, portable phones, tablet computers, personal digital assistants (PDA: Personal Digital Assistant), portable multimedia players (Portable Multimedia Player), televisions, game consoles, watch-type electronic devices, head-mounted displays, personal computer displays, laptop computers, car navigation systems, car dashboards, digital cameras, portable cameras, external advertising boards, electro-optical panels, medical devices, detection devices, refrigerators, washing machines, etc.

[0133] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0134] Material Example 1

[0135] The inorganic semiconductor particles and the first material were added to ethanol at a molar ratio of 1:0.05, and ultrasonicated for 1 hour at room temperature (26° C.) to prepare a mixed solution. The concentration of the inorganic semiconductor particles in the mixed solution was 30 mg / ml.

[0136] Among them, the inorganic semiconductor particles are nano ZnO with an average particle size of 12nm;

[0137] The first material is a compound represented by formula (2).

[0138] Material Example 2

[0139] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0140] The first material is a compound represented by formula (3).

[0141] Material Example 3

[0142] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0143] The first material is a compound represented by formula (4).

[0144] Material Example 4

[0145] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0146] The first material is a compound represented by formula (5).

[0147] Material Example 5

[0148] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0149] The first material is a mixture of the compound represented by formula (6) and the compound represented by formula (3), and the mixing molar ratio is 1:1.

[0150] Material Example 6

[0151] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0152] The molar ratio of the inorganic semiconductor particles to the first material is 1:0.01.

[0153] Material Example 7

[0154] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0155] The molar ratio of the inorganic semiconductor particles to the first material is 1:0.1.

[0156] Material Example 8

[0157] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0158] The molar ratio of the inorganic semiconductor particles to the first material is 1:0.11.

[0159] Material Example 9

[0160] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0161] The inorganic semiconductor particles are nano ZnO doped with Mg, the Mg doping concentration is 5%, and the average particle size is 13 nm.

[0162] Material Example 10

[0163] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0164] The inorganic semiconductor particles are nano-molybdenum oxide with an average particle size of 15 nm; the solvent is changed from ethanol to chlorobenzene.

[0165] Material Example 11

[0166] The scheme of this embodiment is basically the same as that of Material Embodiment 1, except that, in this embodiment,

[0167] The inorganic semiconductor particles are nano-cadmium sulfide with an average particle size of 10 nm; the solvent is changed from ethanol to n-hexane.

[0168] Material Comparative Example 1

[0169] This comparative example is basically the same as Material Example 1, except that in this comparative example, the first material is not added, that is, the preparation steps are:

[0170] The inorganic semiconductor particles were added to ethanol and ultrasonicated at room temperature (26° C.) for 1 hour to prepare a solution. The concentration of the inorganic semiconductor particles in the solution was 30 mg / ml.

[0171] The inorganic semiconductor particles are nano ZnO with an average particle size of 12 nm.

[0172] Material Comparative Example 2

[0173] This comparative example is basically the same as material comparative example 1, except that, in this comparative example,

[0174] The inorganic semiconductor particles are nano ZnO doped with Mg, the Mg doping concentration is 5%, and the average particle size is 13 nm.

[0175] Material Comparative Example 3

[0176] This comparative example is basically the same as material comparative example 1, except that, in this comparative example,

[0177] The inorganic semiconductor particles are nano-molybdenum oxide with an average particle size of 15 nm; the solvent is changed from ethanol to chlorobenzene.

[0178] Material Comparative Example 4

[0179] This comparative example is basically the same as material comparative example 1, except that, in this comparative example,

[0180] The inorganic semiconductor particles are nano-cadmium sulfide with an average particle size of 10 nm; the solvent is changed from ethanol to n-hexane.

[0181] Device Example 1

[0182] The preparation method of the QLED device in this embodiment is as follows:

[0183] (1) A hole injection layer is deposited on a cleaned ITO substrate by spin coating, wherein the material of the hole injection layer is PEDOT:PSS (mass fraction is 2.8%).

[0184] (3) The substrate was transferred to a glove box filled with nitrogen atmosphere, and a chlorobenzene solution of TFB, a material of the hole transport layer, was spin-coated on the surface of the hole injection layer, and then heated at 120° C. for 20 min.

[0185] (4) On the surface of the hole transport layer, a n-hexane solution of quantum dots CdS was spin-coated, and then heated at 100° C. for 5 minutes to prepare a light-emitting layer.

[0186] (5) The mixed solution prepared in Material Example 1 was spin-coated on the light-emitting layer, and then heated at 80° C. for 10 min to obtain an electron transport layer.

[0187] (6) Al is evaporated on the surface of the electron transport layer to form a cathode; wherein the vacuum degree is 3×10 -4 Pa, speed is The time is 1000 s. After packaging, a QLED device is obtained, and the device structure is ITO / PEDOT:PSS / TFB / CdS / ZnO@first material / Al.

[0188] Device Examples 2 to 8

[0189] The scheme of device embodiment n is basically the same as device embodiment 1. The device structure of device embodiment n is ITO / PEDOT:PSS / TFB / CdS / ZnO@first material / Al. The only difference is that in device embodiment n, in step (5), the mixed solution used is changed to the mixed solution prepared in material embodiment n, and n is 2 to 8.

[0190] Device Example 9

[0191] The scheme of device embodiment 9 is basically the same as that of device embodiment 1, except that the device structure of device embodiment 9 is ITO / PEDOT:PSS / TFB / CdS / ZnMgO@first material / Al;

[0192] Correspondingly, in device embodiment 9, in step (5), the mixed solution used is changed to mixed solution 9 prepared in material embodiment 9.

[0193] Device Example 10

[0194] The scheme of device embodiment 10 is basically the same as that of device embodiment 1, except that the device structure of device embodiment 10 is ITO / PEDOT:PSS / MoO3@first material / CdS / ZnO / Al;

[0195] Accordingly, in device embodiment 10:

[0196] In step (3), the chlorobenzene solution of TFB is replaced by the mixed solution prepared in Material Example 10;

[0197] In step (5), the mixed solution used is changed to an ethanol solution of nano ZnO with a concentration of 30 mg / ml.

[0198] Device Example 11

[0199] The scheme of device embodiment 11 is basically the same as that of device embodiment 1, except that the device structure of device embodiment 11 is ITO / PEDOT:PSS / TFB / CdS@first material / ZnO / Al;

[0200] Accordingly, in device embodiment 11:

[0201] In step (4), the n-hexane solution of CdS is replaced by the mixed solution prepared in Material Example 11;

[0202] In step (5), the mixed solution used is changed to an ethanol solution of nano ZnO with a concentration of 30 mg / ml.

[0203] Device Comparison Example 1

[0204] The device comparison example 1 is basically the same as the embodiment 1, except that in the device comparison example 1, the device structure is ITO / PEDOT:PSS / TFB / CdS / ZnO / Al; accordingly, in step (5), the mixed solution used is changed to the mixed solution prepared in the material comparison example 1.

[0205] Device Comparison Example 2

[0206] The device comparative example 2 is basically the same as the device comparative example 1, except that in the device comparative example 2, the device structure is ITO / PEDOT:PSS / TFB / CdS / ZnMgO / Al; correspondingly:

[0207] In step (5), the mixed solution used is changed to the mixed solution prepared in Material Comparative Example 2.

[0208] Device Comparison Example 3

[0209] The device comparative example 3 is basically the same as the device comparative example 1, except that in the device comparative example 3, the device structure is ITO / PEDOT:PSS / MoO3 / CdS / ZnO / Al; correspondingly:

[0210] In step (3), the chlorobenzene solution of TFB is replaced by the mixed solution prepared in Material Comparative Example 3.

[0211] The devices prepared in the above device embodiments and device comparative examples were tested for life and luminous efficiency. The results are recorded in Table 1.

[0212] Life test refers to the time taken for the device brightness to decay to a certain percentage of the maximum brightness under 2mA constant current drive. The time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the life test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life at low brightness is obtained by fitting the decay fitting formula. For example, the life at 1000nits is recorded as T95 1000nits, and the calculation formula is:

[0213] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally it is 1000nits, A is the acceleration factor, which is 1.7.

[0214] The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices. It can be obtained by measuring with EQE optical testing instruments. Among them, the voltage when the brightness of the device reaches 1nite is the turn-on voltage. The specific calculation formula is as follows:

[0215]

[0216] Among them, ηe is the light output coupling efficiency, ηγ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, KR is the radiation process rate, and KNR is the non-radiative process rate.

[0217] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0218] Table 1

[0219] EQE(%) T95@1000nits(h) <![CDATA[L max (nit)]]> Device Example 1 12.42 39.42 4966 Device Example 2 14.52 43.86 5769 Device Example 3 11.77 33.43 4588 Device Example 4 13.16 37.41 5021 Device Example 5 12.54 35.61 4631 Device Example 6 10.11 28.95 4652 Device Example 7 11.73 29.55 4796 Device Example 8 9.42 25.33 4021 Device Example 9 16.45 46.87 6538 Device Example 10 6.44 21.43 3055 Device Example 11 6.85 20.96 3120 Device Comparison Example 1 3.47 9.56 1987 Device Comparison Example 2 4.69 11.85 2175 Device Comparison Example 3 1.78 6.32 1589

[0220] Refer to Table 1, we can see that:

[0221] Device Examples 1 to 8 and Device Example 11 are compared with Device Comparative Example 1, Device Example 9 is compared with Device Comparative Example 2, and Device Example 10 is compared with Device Comparative Example 3. Each device example has higher EQE, L max , T95@1000nits, indicating that by adding the first material into the light-emitting layer, the electron transport layer, and the hole transport layer, it is helpful to extend the service life and light-emitting effect of the device. This may be because the first material can passivate the defects on the surface of the quantum dot light-emitting material, the N-type inorganic semiconductor particles, and the P-type inorganic semiconductor particles, and improve their film-forming effect, thereby playing a role in improving the service life and light-emitting efficiency of the device;

[0222] Further, by comparing device example 1, device example 9, device example 10 and device example 11, it can be seen that compared with their respective corresponding comparative examples, although device example 10 and device example 11 have max , T95@1000nits is also improved, but the improvement is not as great as that of device embodiment 1 and device embodiment 9. This may be because, when the first material is combined with N-type inorganic semiconductor particles, in addition to passivating surface defects and avoiding the formation of electron capture centers and exciton recombination centers on their surfaces, thereby promoting the effective transmission of electrons to the light-emitting layer and the recombination of holes, thereby improving the luminous efficiency of the device, it can also improve the conductivity and transmission performance of the electron transport layer, thereby improving the photoelectric performance of the device.

[0223] The composite materials and preparation methods thereof, optoelectronic devices and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: It comprises inorganic semiconductor particles and a first material, wherein the first material comprises one or more compounds having a structure shown in formula (1); Wherein, Y is selected from one or more combinations of hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C20 alkylcarbonyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted aryl having 5 to 60 ring atoms, substituted or unsubstituted heteroaryl having 5 to 60 ring atoms, substituted or unsubstituted aryloxy having 5 to 60 ring atoms, substituted or unsubstituted heteroaryloxy having 5 to 60 ring atoms, wherein the substituent includes one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, C1-C10 alkylcarbonyl; R1, R2, R3, and R4 are each independently selected from C1-C10 alkyl groups.

2. The composite material according to claim 1, characterized in that Y is selected from one of hydrogen, hydroxyl, C1-C6 alkyl, C1-C6 alkoxy, and NR5R6, wherein R5 and R6 are each independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, and C1-C6 alkylcarbonyl; and / or, R1, R2, R3, and R4 are each independently selected from C1-C4 alkyl groups.

3. The composite material according to claim 2, characterized in that Y is selected from one of H, hydroxyl, C1-C3 alkyl, C1-C3 alkoxy, and NR5R6; and / or, R5 and R6 are each independently selected from H or C1-C2 alkylcarbonyl.

4. The composite material according to claim 3, characterized in that The first material includes one or more compounds represented by any one of formulas (2) to (6):

5. The composite material according to claim 1, characterized in that In the composite material, the molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1); and / or, The average particle size of the inorganic semiconductor particles is 2 to 20 nm.

6. The composite material according to claim 1, characterized in that The inorganic semiconductor particles are selected from N-type inorganic semiconductor particles, and the N-type inorganic semiconductor particles are selected from one or more of metal oxides and doped metal oxides; the metal oxides include one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxides in the doped metal oxides include multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; or, The inorganic semiconductor particles are selected from P-type inorganic semiconductor particles, and the P-type inorganic semiconductor particles are selected from at least one of nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; or, The inorganic semiconductor particles are selected from quantum dot luminescent materials, and the quantum dot luminescent materials include at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds; the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnS At least one of CdS, ZnSe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe e, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, At least one of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

7. A method for preparing a composite material, characterized in that: The following steps are involved: Providing inorganic semiconductor particles, a first material and a first solvent; Mixing the inorganic semiconductor particles, the first material and the first solvent to obtain a composite material; Wherein, the first material includes one or more compounds having a structure shown in formula (1); Wherein, Y is selected from one or more combinations of hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C20 alkylcarbonyl, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted aryl having 5 to 60 ring atoms, substituted or unsubstituted heteroaryl having 5 to 60 ring atoms, substituted or unsubstituted aryloxy having 5 to 60 ring atoms, substituted or unsubstituted heteroaryloxy having 5 to 60 ring atoms, wherein the substituent includes one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, mercapto, cyano, C1-C10 alkyl, C1-C10 alkylcarbonyl; R1, R2, R3, and R4 are each independently selected from C1-C10 alkyl groups.

8. The preparation method according to claim 7, characterized in that: The molar ratio of the inorganic semiconductor particles to the first material is 1:(0.01-0.1); and / or, The first material includes one or more compounds represented by any one of formulas (2) to (6):

9. The preparation method according to claim 7, characterized in that: When the inorganic semiconductor particles include N-type inorganic semiconductor particles, the first solvent includes one or more of C1 to C5 alcohol solvents; or When the inorganic semiconductor particles include P-type inorganic semiconductor particles, the first solvent includes one or more of chloroform, chlorobenzene, and dichlorobenzene; or When the inorganic semiconductor particles include quantum dot luminescent materials, the first solvent includes one or more of n-hexane, n-octane, n-heptane, cyclohexane, and cyclopentane.

10. The preparation method according to claim 7, characterized in that: The step of mixing the inorganic semiconductor particles, the first material and the first solvent to obtain a composite material comprises: The inorganic semiconductor particles, the first material and the first solvent are mixed, and then ultrasonicated for 10 to 240 minutes to obtain a composite material.

11. A photoelectric device, characterized in that: The invention comprises a first electrode, a functional layer and a second electrode, wherein the functional layer comprises at least one first functional layer, and the material of the at least one first functional layer is independently selected from a composite material, and the composite material comprises the composite material according to any one of claims 1 to 6, or comprises a composite material prepared by the preparation method according to any one of claims 7 to 10.

12. The optoelectronic device according to claim 11, characterized in that: The first electrode and the second electrode are each independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or, The thickness of the first functional layer is 10-1000 nm.

13. A display device, characterized in that: Comprising the optoelectronic device according to claim 11 or 12.